Weaving Networks of Change: A Community Intervention to Strengthen the Organization in Los Altos de San Isidro, Atenas - Barrientos Alfaro, María Paula (2024)
The objective of this study was to provide a space for community articulation between the Administrative Association of the Communal Aqueduct and Sewer Systems (ASADA) of Los Altos de San Isidro and other associations in the Atenas canton, with the purpose of promoting organization with respect to the Regulatory Plan and other common needs. As main results, it was found that factors such as affectivity, leadership and bonds are essential to mobilize community commitment and participation. On the other hand, an identity of resistance is identified in the associations that arises from the need for a balance between environmental protection and socioeconomic development of the community. Alternatives such as agroecology, ecological tourism, bioconstruction, among others, are suggested; this in contrast to what is proposed by the local government, as mentioned by the people of the association. From the activities carried out, it was possible to recognize and prioritize the needs of the community, as well as to establish concrete actions to address them.